Chance‐constrained operation of the water‐energy nexus with conflicting objectives. Issue 2 (21st April 2021) - Gao, Ning; Wang, Cheng; Liu, Nian; Bi, Tianshu
Abstract: This paper focuses on the short‐term operation of the water‐energy nexus, where the energy sectors include electricity, natural gas, and heating power. The uncertainties of the renewable generation outputs and the heterogeneous load demands are considered, and their impacts on the operation of the water‐energy nexus are characterised through chance‐constrained modelling. Meanwhile, to achieve a reasonable trade‐off among different conflicting operation goals, such as the out‐of‐the‐pocket energy production costs and the water consumption amount, a bi‐objective decision‐making framework is established. The intractable chance constraints are converted into tractable ones under practical assumptions on the distributions of the uncertainties, where the Gaussian Mixture Model is used to fit the probability density distribution of wind power generation. The nonlinearities and nonconvexities in the proposed model are replaced by their convex approximations. An iterative penalty method is devised to recover the solution feasibility with respect to the original model. A fair compromise between the two conflicting objectives is obtained by the means of Nash bargaining. Simulation results verify the necessity and effectiveness of the proposed model and methods.